Modus Operandi of Transnational Online Gambling Syndicates in the Indonesia-Cambodia Region: Analysis in the Perspective of Transnationalism - Firman Prima Laras; Rusdiyanta (Journal of Social Research, 2025)
Transnational online gambling syndicates in Southeast Asia exploit digital platforms, regulatory gaps, and labor migration to operate across jurisdictions, with Indonesia-Cambodia as a critical nexus. This study examines the syndicates’ modus operandi—recruitment, operational networks, and evasion tactics—through the lens of transnationalism, addressing gaps in state-centric crime analysis. A qualitative case study analyzes secondary data (2020–2025) from academic journals, UN reports, and media, triangulated for validity. Syndicates recruit via social media (Facebook, WhatsApp), exploit migrant labor in Cambodian SEZs, and leverage cryptocurrencies to evade detection. Their fluid networks adapt to law enforcement, highlighting the inadequacy of domestic legal frameworks. The study calls for cross-border collaboration among intelligence, financial, and migration agencies, alongside digital platform regulation, to dismantle these networks. It also urges further research on transnational crime’s financial-digital dimensions and the efficacy of ASEAN cooperation.